The Effect of Quick on The Draw Model Assisted by The Physics Learning Book Integrated Pancasila Values on Critical Thinking Skill - Imam Arifin; Insih Wilujeng; Jumadi Jumadi (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
This research aimed to determine the effect of Quick on The Draw Model assisted by the physics learning book integrated Pancasila values on critical thinking skills. This research is quasi-experimental with one group pretest-posttest design. The subject in this research is 27 students of class XI MIA 2 MAN 1 Yogyakarta. Data collection used a test question to obtain data on students’ critical thinking skills. Data analysis increased critical thinking skills using n-gain. The results show the n-gain value on each indicator of critical thinking as follows: focusing questions of 0.75 (high), answering clarification questions of 0.82 (high), analyzing arguments of 0.68 (moderate), reviewing consideration values of 0.75 (high), and decide on an action of 0.53 (moderate). Therefore, Quick on The Draw Model assisted by the physics learning book integrated Pancasila values can improve critical thinking skills.